Case Report: Precision genetic diagnosis in a case of Dyggve-Melchior-Clausen syndrome reveals paternal isodisomy and heterodisomy of chromosome 18 with imprinting clinical implications - López-Garrido, María-Pilar; Carrascosa-Romero, María-Carmen; Montero-Hernández, Minerva; Serrano-Martínez, Caridad-María; Sánchez-Sánchez, Francisco (Frontiers in Genetics, 2022)
A twelve-year-old patient with a previous clinical diagnosis of spondylocostal skeletal dysplasia and moderate intellectual disability was genetically analyzed through next generation sequencing of a targeted gene panel of 179 genes associated to skeletal dysplasia and mucopolysaccharidosis in order to stablish a precision diagnosis. A homozygous nonsense [c.62C>G; p.(Ser21Ter)] mutation in DYM gene was identified in the patient. Null mutations in DYM have been associated to Dyggve-Melchior-Clausen syndrome, which is a rare autosomal-recessive disorder characterized by skeletal dysplasia and mental retardation, compatible with the patient´s phenotype. To confirm the pathogenicity of this mutation, a segregation analysis was carried out, revealing that the mutation p(Ser21Ter) was solely inherited from the father, who is a carrier of the mutation, while the mother does not carry the mutation. With the suspicion that a paternal disomy could be causing the disease, a series of microsatellite markers in chromosome 18, where the DYM gene is harbored, was analyzed in all the members of the family. Haplotype analysis provided strong evidence of paternal isodisomy and heterodisomy in that chromosome, confirming the pathological effect of this mutation. Furthermore, the patient may have a compromised expression of the ELOA3 gene due to modifications in the genomic imprinting that may potentially increase the risk of digestive cancer. All these results highlight the importance of obtaining a precision diagnosis in rare diseases.